Prevalence of leprosy Cases in Eastern Visayas, Philippines - Almazan, Joseph Uy (International Journal of Advanced Nursing Studies, 2013)
Leprosy is an important global health problem. Moreover, important for its potential to cause progressive and permanent physical disability. However, there is limited study conducted pertaining to the prevalence of leprosy in Eastern Visayas region, as well as to the association of its treatment, population, poverty rate, and gender. This study aimed to explore the prevalence of leprosy in terms of population growth, poverty rate, its treatment, and to determine association between provinces and the type of leprosy treatment for both completed and continuing treatment, between newly diagnosed (2010) and population in its provinces, between average per capita (2001-2009) and continuing treatment of leprosy (2001-2009) between the completed treatment (2001-2009) and population (2001-2009), leprosy cases (2010) between sexes among provinces. It employed descriptive inferential design, and utilizing chi-square test with the used of SPSS version 19. Findings revealed that there were no significant association between provinces and the type of leprosy treatment for both completed and continuing treatment, between newly diagnosed (2010) and provinces, between average per capita (2001-2009) and continuing treatment of leprosy(2001-2009) between the completed treatment (2001-2009) and population (2001-2009), leprosy cases (2010) between sexes among provinces. Finding of this investigation suggests everyone is prone to leprosy, whether or not it’s male or female, and rich or poor. Furthermore, studies identifying other factors like literacy rate, present health status could also be investigated.